2018
DOI: 10.2174/0929866524666170724151917
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Chimeric Protein Based on E Protein Domain III of Tick- Borne Encephalitis Virus and OmpF Porin of Yersinia pseudotuberculosis

Abstract: The newly obtained chimeric antigen could be valuable for the development of the preventing tick-borne encephalitis subunit vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This observation indicated that the EIII protein, which is toxic to the E. coli host cells, obviously cannot be expressed separately from other proteins, which probably masks its toxic effects on producing cells. Therefore, we used the EIII protein produced using the continuous exchange cell-free system, as described earlier [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation indicated that the EIII protein, which is toxic to the E. coli host cells, obviously cannot be expressed separately from other proteins, which probably masks its toxic effects on producing cells. Therefore, we used the EIII protein produced using the continuous exchange cell-free system, as described earlier [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…The plasmids 40HSP70/EIII and 40/EIII were obtained by ligation of the EIII gene into 40HSP70 and pET-40b(+), respectively, at the restriction sites of SacI and SalI. The resultant 40HSP70/EIII and 40/EIII plasmids were used for the expression of chimeric HSP70/EIII protein and the recombinant domain III of TBEV protein E. Since the EIII protein was not expressed separately due to its high toxicity for Escherichia coli cells, we used the EIII protein obtained using the cell-free continuous exchange system, as described previously [ 8 ]. All used primers are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide some clues to the structural basis of the efficient immunogenicity of the OmpF-EIII, we evaluated the intrinsic disorder predisposition of this chimeric protein using a comprehensive computational approach based on the utilization of several tools designed for characterization of various flavors of intrinsic disorder. As described earlier [ 10 ], the amino acid sequence of the chimeric OmpF-EIII protein includes 499 residues:…”
Section: Resultsmentioning
confidence: 99%
“…The domain III (DIII) of E protein is the main antigenic domain, which includes virus-specific epitopes recognized by neutralizing antibodies [ 8 , 9 ]. Therefore, we have constructed the chimeric protein OmpF-EIII based on the fusion of EIII, which consists of DIII and a stem of E protein, and porin OmpF of Gram-negative bacteria Yersinia pseudotuberculosis , for the further development of a subunit anti-TBE vaccine [ 10 ]. Membrane protein OmpF is necessary as a hydrophobic anchor, which allows incorporation of the fusion antigen into the lipid matrix of the nanoparticulate adjuvant and the antigen delivery system, such as the tubular immunostimulating complexes (TI-complexes) [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%